Geographical information system (GIS) based planning technique for forest road network access : case study in Ayer Hitam Forest Reserve - Danney, Arnold (2016)
Forest road is an important infrastructure which is required in forest development timber harvesting activities. It also helps in forest research and environmental damage protection. The forest road specification (Garis Panduan Jalan Hutan, 2010) is used as guideline for forest road planning in Peninsular Malaysia. In this study, a forest road with cost optimization was planned and designed using Geographic Information System (GIS) software, case study in Ayer Hitam Forest Reserve, Selangor. The current forest road was surveyed and tracked using Global Positioning System (GPS) device followed by data analysis in GIS software. For this study, Network Analysis method was used by using Cost Back Link Tool in GIS. This tool developed Network Algorithm which is used to determine the least costly route for forest road. The final output of this method is new forest road network plan of Ayer Hitam Forest Reserve which is generated from the Network Analysis. Results of the study showed the new generated forest road plan has better road network access with least cost construction compare to the current forest road network of AHFR. The road design approach could be applied for planning of forest road in other locations in Peninsular Malaysia.